Experimental Investigation of TDD Reciprocity-Based Zero-Forcing Transmit Precoding. (20th December 2010) - Zetterberg Zetterberg, Per Per
Abstract : We describe an implementation of TDD reciprocity based zero-forcing linear precoding on a wireless testbed. A calibration technique which self-calibrates the base-station without the need for help from other nodes is described. Performance results in terms of downlink channel estimation error as well as bit error rate (BER) and signal to interference noise and distortion ratio (SINDR) are presented for a scenario with two base-stations and two mobile stations, with two antennas at the base-stations and a single antenna at the mobile-station. The results show considerable performance improvements over reference schemes (such as maximum ratio transmission). However, our analysis also reveals that the hardware impairments significantly limit the performance achieved. We further investigate how to model these impairments and attempt to predict the SINDR, such as what would be needed in a coordinated multipoint (CoMP) scenario where scheduling is performed jointly over the two cells. Although the results are obtained for a MISO scenario the general conclusions are relevant also for MIMO scenarios.